Mortality Trends in Patients Hospitalized with the Initial Acute Myocardial Infarction in a Middle Eastern Country over 20 Years - Emad Ahmed; Jassim Al Suwaidi; Ayman El-Menyar; Hajar A. H. AlBinali; Rajvir Singh; A. A. Gehani (Cardiology Research and Practice)
We aimed to define the temporal trend in the initial Acute Myocardial Infarction (AMI) management and outcome during the last two decades in a Middle Eastern country. A total of 10,915 patients were admitted with initial AMI with mean age of 53 ± 11.8 years. Comparing the two decades (1991–2000) to (2001–2010), the use of antiplatelet drugs increased from 84% to 95%, β-blockers increased from 38% to 56%, and angiotensin converting enzyme inhibitors (ACEI) increased from 12% to 36% (P<0.001 for all). The rates of PCI increased from 2.5% to 14.6% and thrombolytic therapy decreased from 71% to 65% (P<0.001 for all). While the rate of hospitalization with Initial MI increased from 34% to 66%, and the average length of hospital stay decreased from 6.4 ± 3 to 4.6 ± 3, all hospital outcomes parameters improved significantly including a 39% reduction in in-hospital Mortality. Multivariate logistic regression analysis showed that higher utilization of antiplatelet drugs, β-blockers, and ACEI were the main contributors to better hospital outcomes. Over the study period, there was a significant increase in the hospitalization rate in patients presenting with initial AMI. Evidence-based medical therapies appear to be associated with a substantial improvement in outcome and in-hospital mortality.